2009
DOI: 10.1007/s12686-009-9008-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of the sharks Rhizoprionodon porosus and R. lalandii by PCR-RFLP and nucleotide sequence analyses of 5S rDNA

Abstract: A molecular approach based on nuclear 5S rDNA sequence variability was applied successfully to correctly identify samples from the two Rhizoprionodon species collected in the wild or sold in markets. The sequence of the non-transcribed spacer (NTS) of the 5S rDNA showed high interspecific variability and no intraspecific polymorphism, making it a useful marker for sharpnose shark identification. Polymorphisms in the NTS sequences of Rhizoprionodon sharks also created unique restriction patterns for each specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Usually, the variation in 5S rDNA is related to the high polymorphism in the NTS regions, whereas the 5S coding region remained unchanged [ 25 , 42 ]. However, in Merlucius fishes [ 28 ], Rajidae rays [ 29 ] and Carcharhinidae sharks [ 30 , 31 ], 5S genes were found to be quite divergent between variant classes and still functional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the variation in 5S rDNA is related to the high polymorphism in the NTS regions, whereas the 5S coding region remained unchanged [ 25 , 42 ]. However, in Merlucius fishes [ 28 ], Rajidae rays [ 29 ] and Carcharhinidae sharks [ 30 , 31 ], 5S genes were found to be quite divergent between variant classes and still functional.…”
Section: Discussionmentioning
confidence: 99%
“…In several vertebrate groups, the main difference between 5S rDNA variants involves the length of the NTS, and are mostly due to single mutations or indels, whereas the transcribed regions of 5S rRNA are not divergent. Conversely, in studies of marine and freshwater fish [ 22 - 28 ], including members of the elasmobranch group such as sharks and rays [ 29 - 31 ], significant variation has been found in spacer sequences and even in the 5S rRNA genes. An extensive analysis of nucleotide sequences and chromosomal in situ hybridization, also in fish, demonstrated that such variant forms correspond to two classes of 5S rDNA repeats, each organized separately in the genome [see 30, for review].…”
Section: Introductionmentioning
confidence: 99%
“…Among many nuclear and mitochondrial markers studied so far, the 5S rDNA is of particular interest in the identification of species because its characteristics make it an ideal specific marker for marine species. In particular, its high degree of conservation means that only universal primers need to be used to amplify it. Further, the flanking of nontranscribed spacers (NTS) between the repeating units of 5S rRNA facilitates amplification and subsequent use as a molecular marker.…”
Section: Introductionmentioning
confidence: 99%
“…However, positive results were obtained by Mendonça et al (2009), who used COI gene and PCR-RFLP to identify two morphologically very similar shark species of the genus Rhizoprionodon (R. lalandii and R. porosus), and by Pinhal et al (2009), who used 5S rDNA amplicons and PCR-RFLP to identify the same species. These results, and that obtained in the present study are already being employed in species identification and conservation plans.…”
Section: Discussionmentioning
confidence: 99%